Papel de mulher: uma visualização de dados sobre a representação feminina no cinema - Nakatsu, Danielle Naomi [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The access to information is one of the most important forms of social empowerment, since it enables the individual to become aware of his or her position within the society, and thus be able to claim equal rights to create change. The designer has the skills to make the information accessible through a variety of tools, one of which is the so-called data visualization, capable of promoting information in a easy and deep way, with the possibility of interpretation by its own user. Therefore, this project intends to develop a digital data visualization, which will be a communication mechanism for the promotion of the feminist movement. As a focus for the project, the films awarded by the Golden Globe Awards from 1995 to 2015 were analyzed in order to collect quantitative and qualitative data about the female characters. Besides the discussion of the presence and representation of women in the cinema, the main objective of this work is to articulate the theoretical content with visuals in order to broaden the debate and disseminate the information. As expected results, this project aims to use information design to disseminate the feminist movement, with greater cultural proximity through the cinema among the mass medias, and creation of an interactive data visualization system

O acesso à informação é uma das mais importantes formas de empoderamento social, uma vez que possibilita que o indivíduo se conscientize quanto sua posição dentro da sociedade e, com isso, seja capaz de reivindicar direitos de igualdade para gerar mudanças. O designer tem competências para tornar as informações acessíveis por meio de diversas ferramentas, sendo uma delas a chamada visualização de dados (data visualization), capaz de promover a informação de forma facilitada ao mesmo tempo que aprofundada, com a possibilidade de interpretação pelo próprio usuário. Nesse sentido, este projeto pretende desenvolver uma visualização de dados digital, o qual seja um mecanismo de comunicação para a promoção do movimento feminista. Como recorte do projeto, foram analisados os filmes premiados pelo Golden Globe Awards (Globo de Ouro) de 1995 a 2015, a fim de coletar dados quantitativos e qualitativos sobre as personagens femininas. Além da discussão da presença e representação da mulher no cinema, o objetivo primordial deste trabalho é articular o conteúdo teórico com imagens de forma a ampliar o debate e disseminar as informações. Como resultados esperados, este projeto visa utilizar o design de informação para difundir o movimento feminista, com maior proximidade cultural pelo cinema dentre as mídias de massa, e criação de um sistema de uma visualização de dados interativo
Keywords: Cinema e mulheres; Feminismo e cinema; Visualização da informação; Women in motion pictures